Smaller scale New Zealand dairy farmers: long term plans and key challenges - Westbrooke, Victoria; Nuthall, Peter; Phillips, Tom (OneFarm/AgriOne Ltd, 2016)
Farmer wellbeing has been defined as “a dynamic process that gives people a sense of how their lives are evolving” (Nimpagariste & Culver, 2010). In order to support and enhance the wellbeing of farmers in New Zealand, the farmers’ goals, future plans and challenges to their plans all need to be understood. A particular group of interest is smaller scale dairy farmers. The average size of dairy farms in developed agricultural nations is increasing and New Zealand is no different. A high proportion (62%) of NZ dairy herds are smaller scale, milking less than 400 cows at peak. Their wellbeing, now and in the future, is important to the New Zealand dairy industry as a whole. Consequently, the aim of this study is to develop an understanding of smaller-scale dairy farmers’ future goals, plans and challenges so that recommendations can be made to enhance and support their wellbeing in the future. Farms who peak milked less than 400 cows were surveyed via telephone. A total of 346 surveys were completed, in Taranaki (n=103), the Waikato (n=144) and Northland (n=99). The majority of respondents’ were owner-operators (75%), male (67%), born and bred in a rural area (79%), and between 40 and 60 years old (57%). Overall, the mean farm size was 97ha, with 240 cows producing 86,789kgMS with 0.83 of a full time employee. Respondents’ had high (67%) equity levels in their businesses and a third (35%) had non-farming investments. Farmers’ most likely future investments were related to their current farming business, that is reducing debt to very low levels and increasing production by more than 10%. Based on farmers future plans and challenges reported and discussed in this study, it is clear the smaller scale dairy farmers would like knowledge and assistance in five key areas; succession, regulation and compliance, staff, technology and cash-flow/profitability. This report concludes with suggestions for each of these areas, which has the potential to maintain or increase the wellbeing of smaller scale dairy farmers in New Zealand. [Executive summary]
Technical Report